Porosity and fluid budget of a water‐rich megathrust revealed with electromagnetic data at the Middle America Trench. (16th November 2016) - Naif, Samer; Key, Kerry; Constable, Steven; Evans, Rob L.
Abstract: At convergent margins, the distribution of fluids released from the downgoing slab modulates the state of stress and seismic coupling at the megathrust plate interface. However, existing geophysical data are unable to quantify the porosity along this interface. Here we use controlled‐source electromagnetic data collected across the Middle America Trench offshore Nicaragua to image the electrical conductivity structure of the outer fore arc. Our results detect a highly conductive channel, inferred to be the region around the décollement, showing the entire section of water‐rich seafloor sediments underthrust with the subducting lithosphere. We use an empirical model of the electrical conductivity of porous media to quantify the channel porosity. Our estimates are consistent with sediment compaction studies, showing a rapid decay of 65%–10% porosity from the trench to 25 km landward. We constrain the channel thickness and use the porosity estimates to determine the water budget, which represents the fraction taken up by fluid. The porosity and water budget estimates show significant lateral variations that we attribute to changes in subducted sediment thickness caused by outer rise bending faults. Between 18 and 23 km from the trench, the conductive channel broadens greatly to 1.5–2 km thick, possibly due to concentrated blind faults or sediment underplating, which suggests a sudden change in hydrogeologic structure at the plate interface. The impact of the anomalous conductor on the seismic coupling and mechanical properties of the megathrust is potentially related to the discrepancy in estimated fault slip between seismic and tsunami source inversions for the 1992 Nicaragua tsunami earthquake. Key Points: Porosity and water content are quantified along the plate interface from controlled‐source electromagnetic data An electrical anomaly that develops at the plate interface may be caused by sediment underplating or concentrated blind faults The relationships between fluid distribution and seismic behavior of the megathrust are discussed